Evaluating multidimensional digital inclusiveness of rice crop manager digital tool: insights from Odisha, India - Singaraju, Niyati; Gakhar, Shalini; Bharti, Preeti; Anjana, V; Mendoza, Jared Jorim (2024)
This report evaluates the inclusiveness and impact of the Rice Crop Manager (RCM) tool in Odisha, India, using the Multidimensional Digital Inclusiveness Index (MDII). Based on a survey conducted across three villages, it explores farmers’ socio-demographic profiles, digital access, and perceptions of the tool’s usability, accessibility, and effectiveness. Findings reveal widespread smartphone ownership but highlight challenges in internet connectivity and digital literacy, with women and educationally underserved users reporting greater barriers. The RCM tool has positively influenced farming decisions and digital skill development, though gaps persist in training accessibility and support mechanisms. Respondents identified additional needs for features like pest management and weather updates. Gender disparities, connectivity issues, and limited co-creation processes emerged as key concerns. The report recommends expanding training programs, improving infrastructure, addressing gender gaps, and fostering user inclusion to enhance the tool’s relevance and sustainability in promoting digital agriculture.